Analiza tendencji rozwojowych kosztów przedsiębiorstwa handlowego przy wykorzystaniu metody indeksowej - Poetschke, Helena (Wydział Prawa i Administracji UAM, 1983)
The article analyses the cost dynamics in a microeconomic scale. The study is conducted on the example of a retail trade enterprise in a longer span of time of 23 years (1953 -1975). The source material has been reduced to statistical comparability. Two variants of comparison were assumed with the adoption of the X965 and 1971 values as constans. The method of economic indexes has been employed in the dynamics analysis. The analysis was carried out in a multivariant mode: in shorter and longer periods of time. The cost variation was examined against commercial activities of the enterprise, establishing several economic causalities. The author made also an attempt at determining usefulness of the method of economic indexes in the analysis of cost dynamics in trade.
Analysis of cost development tendencies in a commercial enterprise with an employment of the index method